2011
DOI: 10.1039/c1cc11909e
|View full text |Cite
|
Sign up to set email alerts
|

The chemistry and complexes of small cyano anions

Abstract: The chemistry of the anions dicyanamide and tricyanomethanide (dca and tcm, respectively) has produced a plethora of discoveries over the past few decades, particularly in relation to transition-metal coordination polymers with magnetic coupling. Over recent years there have been an increasing number of reports of heterofunctionalised cyano-containing anions, typically derivatives of dicyanomethanide. Our own group has been particularly concerned with the amide- and nitroso-functionalised anions carbamoyldicya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(37 citation statements)
references
References 230 publications
0
37
0
Order By: Relevance
“…Therefore, the self-assembly of copper cyanide can generate long-lived and highly efficient luminescent materials with variable structures, which sometimes exhibit intriguing topological architectures. [29,30] CuCN is not a common inorganic salt from the structural point of view. Its 1D chain structure, which is based on twocoordinate metal centers and bridging cyanido ligands, means that CuCN differs from many other inorganic salts characterized by 2D or 3D arrays.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the self-assembly of copper cyanide can generate long-lived and highly efficient luminescent materials with variable structures, which sometimes exhibit intriguing topological architectures. [29,30] CuCN is not a common inorganic salt from the structural point of view. Its 1D chain structure, which is based on twocoordinate metal centers and bridging cyanido ligands, means that CuCN differs from many other inorganic salts characterized by 2D or 3D arrays.…”
Section: Introductionmentioning
confidence: 99%
“…The dcnm anion has been shown to coordinate to lanthanoids through its nitroso group, [25] and in the absence of sterically hindering co-ligands the 12-coordinate homoleptic trianions [LnA C H T U N G T R E N N U N G (dcnm) 6 ] 3À (Ln = La-Gd) are formed (Figure 1b). [26] The trianions [LnA C H T U N G T R E N N U N G (dcnm) 6 ] 3À may be synthesised in high yield, and the previously reported low melting points of their tetraethylammonium salts suggested that an IL may be synthesised when such an anion is coupled with a judiciously selected countercation. Recently, we reported the synthesis of the first series of lanthanoid-based ILs to contain the dicyanonitrosomethanide ligand, (N 4444 ) 3 [LnA C H T U N G T R E N N U N G (dcnm) 6 ] (Ln= La, Ce, Pr, Nd), which displayed polymorph-dependent melting points, as proven by a novel in situ synchrotron-based X-ray powder diffraction technique.…”
Section: Introductionmentioning
confidence: 99%
“…The most habitual strategies to reach this objective are: (i) using simple bridging ligands as cyanide (CN − ) [12], dicyanamide (N(CN) 2 − ) [13][14][15], azide (N 3 − ) [16][17][18][19][20], oxalato (C 2 O 4 2− ) [21], = 3,6-disubstituted-2,5-dihydroxy-1,4-benzoquinone dianion, see Scheme 1). These ligands contain an aromatic ring replacing the central C=C skeleton of oxalato and can also act as bis-bidentate ligands coupling the metal centers they bridge [25].…”
Section: Introductionmentioning
confidence: 99%